Herramientas de productividad en los inventarios: diferencias y similitudes (Prodctivity tools in inventories: similarities and differences) - Mayagoitia Yong, Gabriel; Cruz Álvarez, Jesús Gerardo (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. The domestic, national, or international markets join with the customers demand to the companies, products or services, with excellent design, maximum quality, delivered on time and quantity, to the lowest cost; plus the feasibility to change the production plan and react to new requirements almost immediately. The paper desire is to present an action plan to those that want to use productivity methods focus in the most important element of a global economy, the Inventory. The paper is composing for 2 primary elements: 1) review of the current literature of productivity methods and 2) provide an analysis of those tools about their focus.